2017
DOI: 10.1007/s10897-017-0133-4
|View full text |Cite
|
Sign up to set email alerts
|

Online Module for Carrier Screening in Ashkenazi Jewish Individuals Compared with In‐Person Genetics Education: A Randomized Controlled Trial

Abstract: To increase accessibility to genetics services for low-urgency patients seeking Ashkenazi Jewish (AJ) carrier screening, we designed an interactive computer (IC) module that provides pre-test genetics education and allows genetics professionals to order the test without meeting the patients beforehand. We compared this module with in-person genetic counseling (GC) using a randomized trial. AJ individuals were randomized to undergo genetics education via the IC module (n = 26) or GC (n = 28). We compared post-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…However, this model can be costly and time‐intensive, with variable reimbursement by payers (Cloutier et al, 2017; Leonhard et al, 2017; Lynch et al, 2018). Alternative approaches to service delivery have been shown to be efficient and more affordable without compromising patient knowledge, satisfaction, or decision making (Buchanan et al, 2015; Buchanan, Rahm, & Williams, 2016; Fan et al, 2017; Kubendran, Sivamurthy, & Schaefer, 2017; Pederson et al, 2018; Schwartz et al, 2014; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, 2017). Past efforts in the US have also shown that implementing new SDMs, or SDMs that genetic counselors have not previously used, may increase access to traditionally underserved populations (Mette et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, this model can be costly and time‐intensive, with variable reimbursement by payers (Cloutier et al, 2017; Leonhard et al, 2017; Lynch et al, 2018). Alternative approaches to service delivery have been shown to be efficient and more affordable without compromising patient knowledge, satisfaction, or decision making (Buchanan et al, 2015; Buchanan, Rahm, & Williams, 2016; Fan et al, 2017; Kubendran, Sivamurthy, & Schaefer, 2017; Pederson et al, 2018; Schwartz et al, 2014; Solomons, Lamb, Lucas, McDonald, & Miesfeldt, 2017). Past efforts in the US have also shown that implementing new SDMs, or SDMs that genetic counselors have not previously used, may increase access to traditionally underserved populations (Mette et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Secondary outcomes ( table 1 ) include knowledge , measured using an established questionnaire 33 ; satisfaction with decision-making measured using the Satisfaction with Decision scale 34 ; anxiety measured using the state subscale of the State-Trait Anxiety Inventory, 35 a commonly used psychological assessment tool to measure state anxiety in adult populations including those with chronic conditions; quality of life measured by the 12-item Short Form Survey 36 ; return of results impact measured via the validated Feelings About genomiC Testing Results (FACToR) scale 37 ; empowerment measured via the Genetic Self- Efficacy Scale 38 39 and the six-item Genomics Outcome Scale, derived from the Genetic Counselling Outcome Scale 40 and modified for GS; acceptability measured via the Participant Satisfaction with Genetics Education questionnaire 41 and Web-Based Participants’ Quantitative Feedback Regarding the Interactive Computer Module 41 ; health literacy measured by the BRIEF and Health Literacy Screening tool 42 ; digital health literacy measured by the eHealth Literacy Scale 43 ; attitudes towards healthcare measured by the Health Care System Distrust Scale 44 ; and autonomy in decision-making measured by the Control Preferences Scale. 45 …”
Section: Methodsmentioning
confidence: 99%
“…The following secondary outcomes have been added since the trial registration: Genetic Self-Efficacy Scale 38 39 (added as a pre-test/post-test empowerment scale); Genomics Outcome Scale 40 (added to capture a positive oriented measure for patient impact); Participant Satisfaction with Genetics Education 41 (added as an alternative satisfaction scale); Web-Based Participants’ Quantitative Feedback Regarding the Interactive Computer Module 41 (added to measure participants’ reactions to the tool); FACToR Questionnaire 37 (added as a post-test measure of distress); the 4-Item Brief Health Literacy Screening Tool 42 and the e-Health Literacy Scale 43 (added as baseline measures); Health Care System Distrust Scale 44 and Control Preferences Scale 45 (added for a substudy); and quality of life and costs were added to allow for planned economic evaluations. The Preparation for Decision-Making Scale was removed because it was felt to be redundant with the Satisfaction with Decision-Making and the Decisional Conflict scales.…”
Section: Methodsmentioning
confidence: 99%
“…Pre‐test video education content in particular has been demonstrated to promote patient understanding of ECS (Conijn et al, 2021; Goodhue et al, 2019; Hardy et al, 2018). While video education and other interactive computer modules may not be suitable for all patients (Fan et al, 2018), these and other engaging virtual models may represent a preferred option over traditional text‐based education. For example, the combined storyline and visual images within comic books resulted in higher knowledge scores on ECS surveys compared to those achieved by patients who viewed an ECS video or read an ACOG brochure (Dugger et al, 2021).…”
Section: Recommendationmentioning
confidence: 99%